Simulation of a building heating, ventilating and air-conditioning system - Botha, C P (2013)
Simulation is one of the oldest and also among the most important tools available to engineers. In the building Heating, Ventilating and Air-Conditioning (HVAC) community the availability and/or functionality of simulation tools is limited and it is difficult to determine whether the simulation models accurately represent reality. The purpose of this study was to accurately verify one such a simulation model and then to extend the study to two unique applications. Comprehensive structural, comfort and energy audits were performed to construct a suitable simulation model with the aid of the control simulation package: QUICK Control. The model was then verified against measured building data to ensure an accurate representation of the actual dynamic building response. For the first application various control retrofits were evaluated and the highest potential for energy saving was found. Thereafter the model was implemented to investigate the change in indoor air conditions due to failure of HVAC equipment. Heating, ventilating and air-conditioning in buildings consume a significant portion of the available electrical energy in South Africa. Of this energy up to 30% can be saved by improving the HVAC systems currently installed in the buildings. This could result in savings of up to R400 million. For the building used in this study it was found that up to 66% of the HVAC system’s electrical energy consumption could be saved with a payback period of only 9 months. These savings could be achieved by implementing a setback control strategy with an improved time management procedure. Predicting the impact of failing equipment is a difficult task because of the integrated dynamic effect every HVAC component has on the next. With the aid of a comprehensive integrated simulation model the implications of failing can be determined and necessary assessments and precautions can be taken. The results of this study showed that the air-conditioning system under investigation was approximately 100% over designed. Failure of up to 50% was allowable in the cooling equipment before any noticeable impact could be observed in the indoor climate. With further failure the required comfort conditions could not be sustained. <p The substantial savings calculation and possibility of predicting climate deterioration would not have been possible without the aid of a comprehensive simulation package and model. This study clearly highlights the worth of integrated simulation. === Dissertation (MSc (Mechanical Engineering))--University of Pretoria, 2006. === Mechanical and Aeronautical Engineering === unrestricted